KESENJANGAN GLOBAL DAN PENDIDIKAN : TELAAH LITERATUR TENTANG PERAN SEKOLAH DASAR DALAM MEMBANGUN EMPATI SOSIAL GLOBAL - Nola Seprianti; Nining Dianti; Viony Idelya; Loli Anjeli; Jesika angelina; Heri Effendi; Enjoni (STKIP Subang, 2026)
Global disparities continue to represent a critical issue in contemporary society, particularly regarding differences in economic development, educational access, technological advancement, and social well-being among developed, developing, and underdeveloped countries. These conditions emphasize the need to cultivate global social empathy from an early age through education. This article aims to investigate the contribution of elementary schools in promoting students’ awareness and empathy toward global social issues through a literature review. The study adopts a qualitative descriptive approach by examining and synthesizing findings from scholarly articles, books, and educational policy documents relevant to global inequality and elementary education. The review demonstrates that elementary schools have an important role in introducing students to issues such as poverty, unequal educational opportunities, cultural diversity, and social justice. The incorporation of global perspectives into classroom learning, character education, and multicultural practices can encourage students to develop empathy, tolerance, and a sense of responsibility toward others. In addition, learning activities that promote critical thinking, cooperation, and reflection enable students to better understand the interconnected nature of global challenges. The findings suggest that strengthening global social empathy within elementary education can support the development of responsible and inclusive global citizens. Therefore, integrating global awareness and social empathy into elementary school learning is essential for preparing future generations to contribute to a more equitable and sustainable world.